Evaluation of Dental Golden Ratio in Terms of Facial Esthetics - Petekkaya, Emine; Polat, Sema; Kabakçı, Ayşe Gül; Çevik, Yiğit (SAGE Publications, 2021)
Aim and Objectives: This cross-sectional study examined the Bolton index of 6 maxillary anterior teeth and the facial esthetic ratios in the Turkish population with healthy facial appearance. Materials and Methods: Face photographs of the subjects, taken using a DSLR camera, were fixed in the Frankfort horizontal plane. The measurements were made on the images using ImageJ 1.52a software and certain ratios of face and teeth were calculated such as Bolton index (BI). Differences between genders were evaluated and comparisons with golden ratio of 1.618 were conducted on SPSS. Results: Males had significantly higher upper, middle, lower, and total facial height compared to females ( P < .001, P = 0.0257, P = .0243, P < .001, respectively). Right to left distance of labial commissure (LC)/distance from the distal edge of right canine to the distal edge of left canine ratio had golden proportion. Ratio of naso-menton length to facial width showed golden ratio only in males. The ratio of the width of upper middle incisor to the width of canine tooth also showed golden ratio in both genders. Conclusions: The present study presents noteworthy data about facial and teeth ratios of the young adult Turkish population that will guide plastic surgeons and orthodontists in clinical practice.
Keywords: 3. Good health